Use of The Term Resilience in Adult Cancer Patients: A Systematic Review of A Qualitative Study - La Rakhmat Wabula; Syahfitrah Umamity; Ellen Lombonaung (Health Notions, 2020)
Resilience was a dynamic process that adapts positively to the difficulties it has. This term was often used by researchers in cancer patients. Controversy often occurs in its conception and little is known by patients in the use of the term resilience in their lives. The subject of this paper was cancer patients. The literature review was conducted by examining qualitative studies that discuss the use of terms in cancer patients and the use of themes used in terms of resilience. A systematic review of reviews through SCOPUS, MEDLINE, Psyc INFO and CINAHL reviewed from 2000 to 2017. Thematic analysis was used to encode themes in the studio and produce analytical themes, and resolution resolutions in the studio. After being invited to 573 citations, there were only 32 suitable studies. Four categories emerged, including coping strategies, social support, spirituality, and growth. The conclusion is no use of the term resilience in cancer patients, but cancer patients more often use other terms with the same meaning as resilience. Cancer patients rarely use the term direct resilience, but more often use terms such as coping strategies, social support, growth, and spiritual as terms related to resilience. Keywords: resilience; cancer patients